Cause of Failure of Municipal Waste Water Treatment Plant in Narayanghad - Khanal, Ramesh (SCITECH Nepal, 2020)
Constructed wetland (CW), combined with other physical treatment units, is considered as an environmentally friendly and sustainable option for waste water treatment of varying scale. The absence of mechanical system makes the CW a low maintenance system but not maintenance free. The maintenance free treatment plant concept was observed in municipal waste water treatment plant in Narayanghad, Nepal largely because of its poor maintenance. Due to the absence of maintenance for a long time, sludge from the primary treatment units started to flow to the wetlands which, in turn, caused the reed plant to wither. From different literatures it was found that high organic solid load was the prime cause for the clogging of the filter medium. Clogging triggered oxygen deficiency at the root of the plant and hindered its growth.